Hypertrophic cardiomyopathy in a Clydesdale gelding. Issue 6 (29th April 2018) - Cullimore, AM; Lester, GD; Secombe, CJ; Campbell, K
Abstract : Case report: A 7‐year‐old Clydesdale gelding was referred with a history of progressive lethargy and ventral oedema. The horse developed diarrhoea after treatment with antibiotics by the referring veterinarian. History, clinical signs, imaging and laboratory findings were consistent with hypertrophic cardiomyopathy complicated by antibiotic‐associated colitis. Progression of clinical signs prompted euthanasia and the antemortem diagnosis of hypertrophic cardiomyopathy was confirmed at postmortem examination. Conclusion: Primary HCM is reported as rare in horses, but specific descriptions are lacking. The history, clinical, laboratory and postmortem findings in this case supported a diagnosis of HCM, complicated by antibiotic‐associated colitis.